Case of a Vanishing Colonic Mass. Issue 11 (3rd November 2021) - Barrett, Lisa; Goyal, Abhinav; Davis, Nathan; Govil, Yogesh; Zavala, Stacey
ABSTRACT: Colonic ischemia most often presents with abdominal pain and rectal bleeding. Presentation of colonic ischemia as a prominent mass is exceptionally unique and is not often reported. Concern for neoplasm prompted a repeat scope, which revealed the mass had vanished. We present a case of colonic ischemia, which produced a transient colonic mass formed by inflammatory tissue and clots.